Listeriosis outbreak in South Africa: Are we winning the battle? - Gboyega A Ogunbanjo (South African Family Practice)
South Africa’s listeriosis outbreak has topped the charts as the largest outbreak in history. The first reported case of the current outbreak of listeriosis was in January 2017. On 27 Feb 2018, the South African National Institute of Communicable Diseases (NICD) reported 945 confirmed cases, of which 176 had died (case fatality rate of 19%). Most reported cases were from Gauteng Province (59%, 555/945), followed by the Western Cape (12%, 116/945) and KwaZulu-Natal (7%, 66/945) provinces.1 South Africa is not the only country experiencing outbreaks of listeriosis. Europe has been experiencing a multi-country outbreak since 2015, with a combined number of only 26 cases from Austria, Denmark, Finland, Sweden and the United Kingdom classified as a confirmed microbiological cluster on the basis of whole genome sequencing (WGS) analysis, including core genome multilocus sequence typing (cgMLST) and single nucleotide polymorphism (SNP) based analysis, depending on the country. Four cases have died (case fatality 15.4%).2